2020
DOI: 10.3390/w12020377
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Sand and Its Colour on the South-Eastern Coast of Spain: Implications for Erosion Management

Abstract: Sand colour can give important information about mineral composition and, consequently, sediment source areas and input systems. Beach appearance, which is mostly linked to sand colour, has a relevant economic function in tourist areas. In this paper, the colour of 66 sand samples, collected along both natural and nourished beaches in the western Mediterranean coast of Spain, were assessed in CIEL*a*b* 1976 colour space. The obtained results showed relevant differences between natural and artificially nourishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…(4) In the last 10 years, the 0-m isobaths retreated to land or pushed toward the sea, which is usually expressed as an increase or decrease, respectively, in the area of beach sediments in the section. This factor index is practical for measuring the vulnerability of coasts to erosion (Asensio-Montesinos et al, 2020). We extract the change in the u 4 factor index in the coastal section of each evaluation unit based on the 1:200,000 scale charts published by the China Chart Publishing House (Tianjin) in 2008 and 2017 The value of land contraction regression (m/a) is expressed as a positive value, which reflects an increase in erosion vulnerability; conversely, the negative value of the transgression to the sea reflects a reduction in vulnerability.…”
Section: Data Sources Timementioning
confidence: 99%
“…(4) In the last 10 years, the 0-m isobaths retreated to land or pushed toward the sea, which is usually expressed as an increase or decrease, respectively, in the area of beach sediments in the section. This factor index is practical for measuring the vulnerability of coasts to erosion (Asensio-Montesinos et al, 2020). We extract the change in the u 4 factor index in the coastal section of each evaluation unit based on the 1:200,000 scale charts published by the China Chart Publishing House (Tianjin) in 2008 and 2017 The value of land contraction regression (m/a) is expressed as a positive value, which reflects an increase in erosion vulnerability; conversely, the negative value of the transgression to the sea reflects a reduction in vulnerability.…”
Section: Data Sources Timementioning
confidence: 99%
“…At the same time, sand color in non-urbanized beaches depends on the mineralogical composition, vegetation debris, and degraded organic matter [38]. However, in urbanized areas, sand color can also be related to anthropogenic actions such as beach nourishments that can change the native sand color with different environmental and economic impacts [39,40]. Another explanation of the physical parameter's results are the CPCV sandy beaches could be the erosion of sandy cliffs, which may have contributed in part to the dark tan color of the sand [41].…”
Section: Physical Parameters In Urban Beachesmentioning
confidence: 99%
“…Moreover, nourishing with sand dissimilar from the native mineralogical composition can result in changes in beach sand color, which impacts visitor appreciation, with light colored nourished sediment being preferred by visitors in some cases, such as seen in Cuba and Italy 172,206 . Comparisons of natural and nourished beaches in Spain showed that nourished beaches have distinct different colors (quantified using the CIEL*a*b* methodology) which can persist for years after sand is added 207 .…”
Section: [H2] Social and Economic Impactsmentioning
confidence: 99%